Relationship between methods for assessing electrical conductivity and concentration of soluble cations in soils from Costa Rica - Campos-Granados, María Fernanda (2025)
Introduction. The electrical conductivity of saturated paste extract (EC(e)) is the reference method for assessing the impact of soil salinity on crops. However, this method has drawbacks that limit its reproducibility in the laboratory. Previous studies have related EC(e) to EC measurements conducted on various soil/water extractions. However, due to the variability of soils and methods employed, specific local validations are needed for soils in Costa Rica. Objective. To establish the relationship between EC(e) and EC measurements in soil/water extractions (1:2,5) and (1:5), and to validate the relationship between EC and the sum of soluble cations (SC) in soil extracts and water samples in Costa Rica. Materials and methods. EC was measured in Costa Rican soils using three methodologies: saturated paste extract, (1:2,5) volumetric ratio extractions, and (1:5) mass/volume ratio extractions. Soluble cations (Ca, Mg, K, Na) were quantified by ICP-OES in both soil extracts and water samples. Conversion factors (fc) between EC(1:2,5)/EC(1:5) and EC(e), as well as the EC-SC relationship, were determined through regression analysis. Results. The fc values obtained for EC(1:2,5)-EC(e) and EC(1:5)-EC(e) were 3,00 and 4,30, respectively. Based on these fc, critical EC(1:2,5) and EC(1:5) values were established for sensitive and moderately sensitive crops to salinity. The strong linear EC-SC relationship validated the use of the proportionality factor K = 10 to estimate SC (mmol(+) L⁻¹) from EC (dS m⁻¹) data. Conclusions. The (1:2,5) and (1:5) extractions are practical methods for estimating EC(e), and these results will allow to standardize the EC interpretation and soil salinity diagnosis in soils from Costa Rica. The EC-SC relationship supports the use of EC as a proxy for the total concentration of soluble salts in soils extracts and water samples in Costa Rica.